THE STATE OF AGRICULTURAL DEVELOPMENT AT THE LOCAL LEVEL - Zhangalieva, Y. S. (ЗКАТУ им. Жангир хана, 2022)
The article identifies the current state, dynamics, priority areas of agricultural development of Uralsk, West Kazakhstan region, the ways of improvement. Monographic, analysis and synthesis, statistical and economic methods were used in writing the article. The results of the agricultural industry for 2018-2020 for the city were analyzed. The dynamics of such indicators as the number of cattle and poultry, their productivity is shown. The structure of production by categories of agricultural formations, as well as analyzed the total volume of their agricultural production. The article reflects the potential of livestock production, the provision of own resources, the sustainable growth of agricultural production, the directions of budgetary policy for sustainable development of crop production, and all this should be implemented within the framework of state programs..
Zhangalieva, Y. S. THE STATE OF AGRICULTURAL DEVELOPMENT AT THE LOCAL LEVEL / Y. S. Zhangalieva, Е. С. Жангалиева. - Текст : непосредственный // Ғылым және білім: Қазіргі көзқарас жағдайындағы ғылым мен білімді дамытудың өзекті мәселелері: ХХІІ халықаралық ғылыми-практ. конф. материалдары (12 сәуір 2022 ж.) = Наука и образование: Актуальные вопросы развития науки и образования в условиях современных вызовов: мат. ХХІІ междунар. науч.-практ. конф. (12 апреля 2022 г.) = Science and education: topical issues of the development of sciense and education in the context of modern challenges: mat. of the XXII International Scientific and Practical Conf. (12 aptil 2022). - Уральск: ЗКАТУ им. Жангир хана. - 2022. - № 2 (67) : прил. № 2. - Р. 382-388 (Uralsk).
Keywords: agro-industrial complex; agriculture; livestock; crop production; cattle; milk; meat; agrarian sector; зкату; научный журнал